Multi-stages Aesthetic Refinement Following Anterolateral Thigh Free Flap for Head and Neck Reconstruction - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Arina, Maryam Nur (Lingkar Studi Bedah Plastik Foundation, 2020)
Introduction: Multi-stages refinement of a bulky flap after composite defects reconstruction of multiple facial units has been a challenging situation. Goals including restoration of periorbital and malar area and redefining the aesthetic aspects of the units as well as the surrounding nasolabial area with multiple refinements and microfat graft. Methods: A 50-year-old male patient with a history of solitary fibrous tumor underwent wide excision of left periorbital, infraorbital, lateral nasal sidewall, and malar area. The defect is enclosed with Anterolateral Thigh Free Flap (ALT). Bulkiness of the flap, sunken left nasolabial, and asymmetric alar nasal unit were found during outpatient follow-up. These problems lead to the necessity of refinement procedure to reduce the bulkiness to improve the aesthetic outcome of the patient. Microfat graft was the method chosen to volumized the sunken nasolabial and asymmetric alar nasal unit. Results: Patient is satisfied with the result due to improvement of alar nasal units symmetricity and reduced bulkiness of the flap area. No complication was observed. Conclusion: Meticulous planning and staging of the surgical refinement procedures in conjunction with microfat graft results in good aesthetic outcome and satisfies the patient and reduces the possibility of complications.